Reprogramming the immune system using antibodies. - Graca, L; Waldmann, H (2006)
Tolerance induction induced by monoclonal antibodies or co-receptor blockade is robust enough to resist breakdown by adoptive transfer of lymphocytes. Such resistance, the hallmark of dominant tolerance, is mediated by CD4+ regulatory T cells. CD4+CD25+ T cells inhibit lymphopenia-mediated accumulation of T cells in vivo, but caution should be exerted when investigating antigen-specific regulation in replete mice. A number of different deletional and tolerogenic processes following antibody-induced tolerance are discussed in this chapter, including activation-induced cell death, immunosuppressive cytokines, and immunoprivileged sites. The possibility of spreading tolerance to other cells, including parenchymal cells, is also discussed. This chapter emphasizes recent evidence that shows that self-tolerance does not rely on several mechanisms running independently, but rather a continuum of synergistic and overlapping mechanisms.